Reduction in the number of binary variables for inter-sample avoidance in trajectory optimizers using mixed-integer linear programming - Afonso, Rubens J. M.; Galvão, Roberto K. H.; Kienitz, Karl H. (International journal of robust and nonlinear control, 2016)
Summary This note proposes the use of a tuple encoding scheme to reduce the number of binary variables involved in trajectory optimization problems with inter‐sample avoidance constraints. Copyright © 2016 John Wiley & Sons, Ltd.